2006
DOI: 10.1111/j.1365-2222.2006.02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of in vivo basophil activation in chronic idiopathic urticaria

Abstract: Basophil activation marker expression is increased in CIU subjects and is not associated with serum factors. In addition, serum HRA and FcepsilonRIalpha immunoreactivity are not unique to CIU, or related to enhanced circulating basophil marker expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 43 publications
4
77
0
2
Order By: Relevance
“…An increasing number of studies has confirmed the usefulness of BAT with donor basophils in the diagnosis and pathogenetic elucidation of chronic urticaria [129,130,131,132,133,134,135,136,137,138]. …”
Section: Clinical Indications Of Batmentioning
confidence: 99%
“…An increasing number of studies has confirmed the usefulness of BAT with donor basophils in the diagnosis and pathogenetic elucidation of chronic urticaria [129,130,131,132,133,134,135,136,137,138]. …”
Section: Clinical Indications Of Batmentioning
confidence: 99%
“…9,11 Upregulation of CD203c on peripheral blood basophils from patients with CU has also been described. 12 In the current study, we sought to compare the effect of sera from ASST 1 and ASST -patients with CU on basophil CD203c expression to normal control sera and to determine the correlation with BHR. In addition, IgG depletion of sera from ASST 1 individuals was performed to determine whether the mechanism of CD203c upregulation is IgG-mediated.…”
mentioning
confidence: 99%
“…Diğer çalışmalarda tedaviye yanıt ve hastalık seyri ile ilişkisi bulunamamış olması da OST'nin güvenilirliğini şüpheye düşüren kanıtlar arasında yer almaktadır (14). (20). Bu çalışma sonuçları otoantikorların işlevsiz olduğu yönünde kanıtlar sunmaktadır.…”
Section: Patogenez Teorileri -Otoimmün Teori;unclassified